Thermophysical properties of Inconel alloy 740 modified with titanium and aluminium - Kim, Daeho; Jung, Woosang; Lee, Sanghyun (Inderscience Publishers, 2020)
Superalloys, which are known for their high temperature resistance, are widely used in aerospace applications, gas turbines, turbine blades for jet engines and automotive applications. The Inconel alloy 740 is a nickel-based, age-hardened superalloy, with good heat resistance and thermal stability. The thermophysical properties of the Inconel alloy 740 of varied material compositions were assessed by measurement of the thermal diffusivity, specific heat capacity, thermal conductivity, and coefficient of thermal expansion (CTE). Inconel alloy 740 was modified with titanium and aluminium. A typical IN740 alloy, 'IN1', had Ti (2.8 wt.%) and Al (1.4 wt.%) added, 'IN2' was modified using Ti (3.6 wt.%) and 'IN3' was modified with Al (1.8 wt.%). The thermal diffusivity and the specific heat capacity were measured using laser flash and differential scanning calorimetry, respectively. The thermal conductivity was calculated according to the results of the thermal diffusivity and specific heat capacity in the temperature range from room temperature to 800 degrees C. The CTE was evaluated by push-rod dilatometer method. In this study, we present the thermophysical properties of the Inconel alloy 740, of which the base material was modified with titanium and aluminium.